Relationship between service quality and customer satisfaction in outdoor services activities: a case study of Rentas Adventure Group / Nurul Hasanah Abdul Razak - Abdul Razak, Nurul Hasanah (2021)
The aim of this is identify the relationship between service quality and customer satisfaction in the outdoor activities service which was provided by Rentas Adventure Group. The SERVQUAL model was adopted to measure the service quality provided which contributes to customer satisfaction. Questionnaires were distributed to 250 customers of Rentas Adventure Group. Easy random sampling technique was used to determine the sample size and 218 respondents had given their prompt feedback towards the questionnaire distributed. Research questions and objectives were set. Descriptive statistics comprising the percentage, the mean and standard deviation were used for data presentation and analysis. Correlation analysis was employed to evaluate the relationship between service quality and customer’s satisfaction. The study reveals that service quality has an effect on customer satisfaction and that there is a relationship between service quality and customer satisfaction. The researcher concluded that the organization needs to enhance and monitor their service quality regularly because of its effects on customer satisfaction. To ensure that customer satisfaction level is high, organisations must first of all know the expectations of the customers and how they can meet such expectations. In ensuring the customer’s satisfaction could be improved, the organizations recommended to seek for the feedback from the customers as they could improve it in the future.